An Explorative Biomarker Study for Vaccine Responsiveness after a Primary Meningococcal Vaccination in Middle-Aged Adults - van der Heiden, Marieke; Berbers, Guy A. M.; Fuentes, Susana; van Zelm, Menno C.; Boots, Annemieke M. H.; Buisman, Anne-Marie (Frontiers in Immunology, 2018)
Introduction Prevention of infectious diseases in the elderly is essential to establish healthy aging. Yet, immunological aging impairs successful vaccination of the elderly. Predictive biomarkers for vaccine responsiveness in middle-aged adults may help to identify responders and non-responders before reaching old age. Therefore, we aimed to determine biomarkers associated with low and high responsiveness toward a primary vaccination in middle-aged adults, for which a tetravalent meningococcal vaccine was used as a model. Methods Middle-aged adults (50–65 years of age, N = 100), receiving a tetravalent meningococcal vaccination, were divided into low and high responders using the functional antibody titers at 28 days postvaccination. A total of 48 parameters, including absolute numbers of immune cells and serum levels of cytokines and biochemical markers, were determined prevaccination in all participants. Heat maps and multivariate redundancy analysis (RDA) were used to reveal immune phenotype characteristics and associations of the low and high responders. Results Several significant differences in prevaccination immune markers were observed between the low and high vaccine responders. Moreover, RDA analysis revealed a significant association between the prevaccination immune phenotype and vaccine responsiveness. In particular, our analysis pointed at high numbers of CD4 T cells, especially naïve CD4 and regulatory T subsets, to be associated with low vaccine responsiveness. In addition, low responders showed lower prevaccination IL-1Ra levels than high responders. Conclusion This explorative biomarker study shows associations between the prevaccination immune phenotype and vaccine responsiveness after a primary meningococcal vaccination in middle-aged adults. Consequently, these results provide a basis for predictive biomarker discovery for vaccine responsiveness that will require validation in larger cohort studies.